Anion-π Interactions of Hexaaryl[3]radialenes - Evans, J.; Hollis, C.; Hack, S.; Gentleman, A.; Hoffmann, P.; Buntine, Mark; Sumby, C. (American Chemical Society, 2012)
Coordination polymers and discrete metallo-supramolecular assemblies of hexaaryl[3]radialene compounds exhibit intriguing structures with short anion to π-centroid distances in the solid-state. Furthermore, these [3]radialene compounds display useful photophysical and electrochemical properties that make them ideal as potential platforms for anion receptors. In this study, hexafluoro[3]radialene was optimized to the MP2/aug-cc-pVTZ level of theory, and its complexes with halide anions were optimized to HF/6-31G+ +(d,p), MP2/6-31G++(d,p), M06-2X/6-31G++(d,p), and M06-2X/6-311G++(d,p) levels of theory. Hexafluoro[3]radialene was shown to have properties (large positive Qzz and areas of positive electrostatic surface potential) comparable to other compounds that show anion- π interactions. The interaction energies of complexes of hexafluoro[3]radialene with halide anions were calculated and found to be favorable and equivalent to those of fluorinated aromatic compounds. A series of synthetically accessible hexaaryl[3]radialenes were optimized to HF/6-31G++(d,p) theory and their complexes with halides optimized to the M06-2X/6-31G++(d,p) level of theory. The calculated properties of the electron-deficient hexaaryl[3]radialenes also show large positive Qzz quadrupole moments and two areas of positive potential; at the [3]radialene core and the acidic aryl hydrogen atoms. The interaction energies of the complexes of hexaaryl[3]radialenes and halide anions were found to follow the trend F- > Cl- ˜ Br- and correlate with the electron-deficient nature of the [3]radialene.Close contacts were observed between the anion and the radialene core and the aryl hydrogen atoms, suggesting a combination of anion- π and hydrogen bonding is important. Mass spectrometry was used to experimentally observe the complexes of a number of hexaaryl[3]radialenes with F-, Cl-, and Br- predicted computationally. Anion-[3]radialene complexes were successfully detected, and the stability of the complexes in tandem MS/MS experiments was found to support the computational results.